ROBERT ENTMAN FRAMING ANALYSIS OF PRABOWO SUBIANTO’S IMAGE IN REPUBLIKA.CO.ID MARCH – APRIL 2019 EDITION - Launa Launa (Pusat Penelitian dan Pengembangan Aplikasi Informatika, Informasi dan Komunikasi Publik (APTIKA dan IKP) Badan Penelitian dan Pengembangan SDM Kementerian Komunikasi dan Informatika, 2020)
The political campaign-style of a political actor determines the public acceptance of his self-image and leadership image. This study focuses on discussing the framing of Republika.co.id news related to Prabowo Subianto's (PS) self-image and leadership image in the 2019 presidential election. Image is the main element that a political leader must have, and the construction of a leader image in a media is certainly related to interests. construction news media concerned. Through the use of Robert Entman's four model framing analysis tools, this study tries to reveal the Republika Online (ROL) framing of PS self-image and leadership image. The results showed, positive ROL framing related to self-image and leadership image. PS: PS is a populist and critical figure of Jakarta elites whose life orientation is only to enrich themselves in the middle of their poor people's lives; PS is a figure of a people's leader who can create a better life; PS is a leader whose life is quite well established; if elected (as president) PS will only devote himself to the people, improve the quality of people's lives, and ensure justice for all the people